#### Answer

$t=\dfrac{rs}{q-r}$

#### Work Step by Step

Using the properties of equality, in terms of $
t
$, the given expression, $
qt=r(s+t)
$, is equivalent to
\begin{array}{l}
qt=rs+rt
\\\\
qt-rt=rs
\\\\
t(q-r)=rs
\\\\
t=\dfrac{rs}{q-r}
.\end{array}

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$t=\dfrac{rs}{q-r}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.